The effect of Aβ seeding is dependent on the presence of knock-in genes in the AppNL−G−F mice - Lacoursiere, Sean G.; Safar, Jiri; Westaway, David; Mohajerani, Majid H.; Sutherland, Robert J. (Frontiers in Dementia, 2022)
Alzheimer’s disease (AD) is characterized by the prion-like propagation of amyloid- (A). However, the role of A in cognitive impairment is still unclear. To determine the causal role of A in AD, we intracerebrally seeded the entorhinal cortex of two-month-old AppNL-G-F mouse model with an A peptide derived from patients who died from rapidly progressing AD. When the mice were three months of age or one month following seeding, spatial learning and memory were tested using the Morris water task. Immunohistochemical labeling showed seeding with the A was found accelerate A plaque deposition and microgliosis in the AppNL-G-F mice but this was dependent on the presence of the knocked-in genes. However, we found no correlation between pathology and spatial performance. The results of the present study show that the seeding effects in the AppNL-G-F knock-in model, and these are dependent on the presence of a humanized App gene. But these pathological changes were not initially causal in memory impairment.